1982
DOI: 10.1128/iai.37.3.1132-1137.1982
|View full text |Cite
|
Sign up to set email alerts
|

Protection against lethal challenge of BALB/c mice by passive transfer of monoclonal antibodies to five glycoproteins of herpes simplex virus type 2

Abstract: Monoclonal antibodies secreted by six hybridomas and recognizing antigenic sites on glycoproteins gC, gAB, gD, gE, and gF of herpes simplex virus type 2 were examined for their ability to protect BALB/c mice from lethal infection by the virus. Administration of monoclonal antibodies to individual glycoproteins intraperitoneally 3 h before footpad challenge with 10 times the 50% lethal dose of virus protected between 35 and 75% of the mice, except for one of two monoclonal antibodies recognizing antigens on gC.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(68 citation statements)
references
References 26 publications
4
64
0
Order By: Relevance
“…Furthermore, we have previously demonstrated that gD subunit immunization (without adjuvants) elicits neutralizing antibodies without the induction of a detectable CD4 ϩ CTL response and still protects mice from HSV-2 vaginal challenge (9). In addition, the ability of anti-gD antibodies to protect mice in the absence of a cellular response was demonstrated by a number of passive transfer studies with monoclonal anti-gD antibodies (2,23,55,68,71). Moreover, it was shown that the Th1-like IgG2a monoclonal anti-gD antibody was superior to the IgG1 monoclonal anti-gD antibody with regard to the relative efficacy of the passive protection conferred (24).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we have previously demonstrated that gD subunit immunization (without adjuvants) elicits neutralizing antibodies without the induction of a detectable CD4 ϩ CTL response and still protects mice from HSV-2 vaginal challenge (9). In addition, the ability of anti-gD antibodies to protect mice in the absence of a cellular response was demonstrated by a number of passive transfer studies with monoclonal anti-gD antibodies (2,23,55,68,71). Moreover, it was shown that the Th1-like IgG2a monoclonal anti-gD antibody was superior to the IgG1 monoclonal anti-gD antibody with regard to the relative efficacy of the passive protection conferred (24).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have looked at the ability of mAbs to protect against HSV infection. Early papers showed that both neutralizing anti-gD and gC mAbs and nonneutralizing anti-gD, gC, gB, gD, and gE mAbs could protect against lethal footpad challenge in mice (Balachandran et al, 1982;Dix et al, 1981). The latter study found that a mixture of mAbs had an efficacy corresponding roughly to the sum of that of the individual mAbs and that protection was equally apparent in C5-deficient mice.…”
Section: Herpesvirusesmentioning
confidence: 99%
“…Attempts have been made to correlate the ability to protect with activity and in vitro functional assays, i.e., antibody and complement-mediated cytotoxicity (CMC), antibody-dependent cellular cytotoxicity (ADCC), and neutralization with or without complement. However, such associations have not been conclusively demonstrated [3][4][5]. In the present study we vaccinated guinea pigs with a HSV 1 subunit vaccine [6], and subsequently challenged them intravaginally with HSV 2.…”
Section: Introductionmentioning
confidence: 78%